Major cardiac and vascular complications after transvenous lead extraction: acute outcome and predictive factors from the ESC-EHRA ELECTRa (European Lead Extraction ConTRolled) registry. Issue 5 (27th December 2018) - Zucchelli, Giulio; Di Cori, Andrea; Segreti, Luca; Laroche, Cécile; Blomstrom-Lundqvist, Carina; Kutarski, Andrzej; Regoli, François; Butter, Christian; Defaye, Pascal; Pasquié, Jean Luc; Auricchio, Angelo; Maggioni, Aldo P; et al.
Abstract: Aims: We aimed at describing outcomes and predictors of cardiac avulsion or tear (CA/T) with tamponade and vascular avulsion or tear (VA/T) after transvenous lead extraction (TLE) in the ESC-EHRA European Lead Extraction ConTRolled (ELECTRa) registry. Methods and results: A total of 3555 consecutive patients of whom 3510 underwent TLE at 73 centres in 19 European countries were enrolled. Among 58 patients (1.7%) with procedure-related major complications, 49 (84.5%) patients (30 CA/T and 19 VA/T) presented cardiovascular complications requiring pericardiocentesis, chest tube positioning and/or surgical repair. The mortality was 20% in patients with tamponade due to CA/T and 31.6% in patients with VA/T. Pericardiocentesis as first manoeuvre followed by rescue surgical repair was highly effective in case of CA/T (93.8%). At multivariate analysis, CA/T with tamponade was more common in RIATA lead extraction, female patients, leads with a mean dwelling time more than 10 years, and when ≥3 leads were extracted or multiple sheaths required. Occlusion or critical stenosis of superior venous access and the leads mean dwelling time more than 10 years were independent predictors for VA/T, while mechanical dilatation was an independent predictor of a lower incidence of this complication as compared to the use of powered sheaths. Conclusions: In the ELECTRa registry, RIATA lead extraction and superior venous access occlusion/thrombosis are two new independent predictors for cardiac tamponade and major vascular complications, respectively. The use of mechanical sheaths seems to be associated with a lower incidence of VA/T. A strategy of pericardiocentesis followed by a rescue surgical approach seems to be reasonable in order to treat a CA/T with tamponade.